Diabetic ketoacidosis with acute kidney injury in prepubertal children: a report on two cases - Dwi Andriyani; Afriyan Wahyudhi; Shirley Leonita Anggriawan (Indonesian Pediatric Society, 2016)
Type 1 diabetes mellitus is a result of autoimmune damage, in which environmental factors are thought to trigger the autoimmune destruction of pancreatic ÃŸ-cells.1,2 Worldwide, an estimated 65,000 children under 15 years of age develop type 1 diabetes mellitus each year.3 Approximately 30% of children who present with newly-diagnosed type 1 diabetes have diabetic ketoacidosis (DKA).4 Himawan et al. reported a DKA prevalence of43.6% in girls.5 The long-term effects of diabetes mellitus include retinopathy, chronic kidney disease (nephropathy), neuropathy, and dyslipidemia.2